Awareness of rabies and its prevention among adults in urban slums of Tiruvallur district - M., Vijayalakshmi; M., Vijay Chandran (International Journal Of Community Medicine And Public Health, 2021)
Background: Rabies is an acute fatal encephalomyelitis caused by a Lyssavirus type 1 is recognized today because of its global distribution, incidence, veterinary and human health costs, and extremely high case fatality rate .The large number of deaths due to rabies can be attributed to the fact that in spite of availability of effective vaccination against rabies, people are unaware of various aspects and its prevention. Objective was to study the awareness about Rabies and its prevention among adults in urban slum area of Tiruvallur district. Methods: The present study was a cross sectional study conducted over a period of 2 months between December 2019 to January 2020 in an urban slum area of Tiruvallur district of Tamilnadu. A Semi Structured questionnaire was administered to the study participants and the data was analysed by SPSS 16. Results: Among 295 study participants, Mean age was 34.73 (+or-10.26) years. Majority (38.6%) of the respondents were of the age group 20-29 years and 60.3% were male participants. 98.6% had heard about rabies and 83.7% knew that Rabies is a fatal disease. Majority (95%) consult a Doctor immediately and 65% knew correctly about a first aid after animal bite. 87% of the study participants were aware of antirabies vaccine. Age and educational status were significantly associated with rabies awareness (p<0.05). Conclusions: Most of the study participants were aware of rabies. Awareness was high among younger people and educated people. Effective health education shall help in rabies prevention.